The Effect of the Existence of Krueng Geukuh Port on Regional Development in Dewantara District North Aceh Regency - Nikmatoel Sahara; A. Rahim Matondang; H. B. Tarmizi (Budapest International Research and Critics University, 2022)
The existence of the Krueng Geukueh port in North Aceh Regency has made the local community experience changes. The immediate positive impact is the development of the economic sector. The area that was once deserted has now turned into a bustling area with community activities taking advantage of the existence of the port. The objectives of this study are to: 1) analyze the effect of the existence of Krueng Geukueh Port on the growth of community economic activities in Dewantara District, North Aceh Regency, and 2) Analyze the influence of the existence of Krueng Geukueh Port which includes road accessibility, road physical conditions, improvement of land use, and protection. Environment for regional development in Dewantara District, North Aceh Regency. The research was conducted in North Aceh Regency on the Effect of the Existence of Krueng Geukuh Port on Regional Development of Dewantara Subdistrict, North Aceh Regency. The analytical method used in this research is the different t test and multiple regression analysis with the number of respondents as many as 99 people. The results showed that the existence of Krueng Geukueh Port in Dewantara District, North Aceh Regency had a positive impact on job opportunities and business opportunities for the community around Krueng Geukueh Port in Dewantara District, North Aceh Regency and showed a significant difference before and after doing business in locations around Krueng Geukueh Port. in Dewantara District, North Aceh Regency. Simultaneously and partially the existence of Krueng Geukueh Port in Dewantara District, North Aceh Regency which includes accessibility, physical condition of the road, improvement of land use and environmental protection has a positive and significant influence on development.